Influence of antibrowning solutions, air exposure, and ultrasound on color changes in fresh‐cut apples during storage. Issue 6 (20th March 2017) - Putnik, Predrag; Bursać Kovačević, Danijela; Herceg, Korina; Levaj, Branka
Abstract: This study identified optimal apple cultivars and antibrowning treatments with/without ultrasound for fresh‐cut processing with minimal color changes observed during storage. Color changes ( Δ E a, b ∗ ) were evaluated for various apple cultivars (Idared, Golden Delicious, Gala, Gloster, Cripps Pink, Braeburn, and Fuji) treated with different antibrowning solutions (ascorbic + citric acid; ascorbic acid + NaCl; NaCl, citric acid, and Ca‐ascorbate) with/without ultrasound during storage of 24 hr. Also, sensory evaluation was conducted to assess the acceptability of treated apples. The effectiveness of antibrowning treatments with or without ultrasound were determined as negative effect on Δ E a, b ∗ and browning index over the storage. The best apples were Cripps Pink and Golden Delicious, and solutions were Ca‐ascorbate and ascorbic + citric acid. In combination with ultrasound, the best solution was Ca‐ascorbate. Exposure to ultrasound confirmed the best suitability of Ca‐ascorbate and Cripps Pink for fresh‐cut, while implying that longer periods of exposure might be beneficial for prevention of browning in fresh‐cut apples. Practical applications: Fresh‐cut processing is a significant segment of the worldwide food markets, with fresh‐cut apples being one of the most important foods for such production. Fresh‐cut apples have short shelf‐life that is mainly reduced by browning. Since, profit margin in fresh‐cut industry is spread over the short periods of time (largely due to short shelf‐life) it is crucial for such industrial processing to identify apples and antibrowning treatments that will extend preservation to longest possible time while assuring consumer acceptance of such products. Simultaneously, it is important to detect advanced nonthermal treatments able to reduce or prevent browning in fresh produce with minimal loss in nutritive value and addition of additives, due to consumers' tendency to demand such foods.